2003
DOI: 10.1136/gut.52.7.960
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, correlates, and characteristics of undetected coeliac disease in England

Abstract: Objective: To examine the seroprevalence, correlates, and characteristics of undetected coeliac disease in a large adult population sample in Cambridge, UK. Methods: The Cambridge General Practice Health Study invited individuals from 12 general practices, aged 45-76 years, to attend for a health survey that included a bone density measurement, between 1990 and 1995. A total of 7550 participants' serum samples were tested for antiendomysial antibody (EMA). Seroprevalence of undetected coeliac disease was based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
199
5
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(231 citation statements)
references
References 28 publications
(20 reference statements)
20
199
5
7
Order By: Relevance
“…Similar studies in Brazil and India also found twice the CD frequency in children [7,8] . However, these data are in contrast with the observed prevalence in adult populations from European countries such as the United Kingdom (1.2%) [9] and, more surprisingly, Finland, where a 2.4% prevalence of CD was demonstrated by biopsy in a population of adults over fifty years of age [10] . The pediatric population was not analyzed in these studies, but prevalence of over 1%, even in older populations, is similar to that observed in pediatric studies.…”
Section: Epidemiologycontrasting
confidence: 52%
“…Similar studies in Brazil and India also found twice the CD frequency in children [7,8] . However, these data are in contrast with the observed prevalence in adult populations from European countries such as the United Kingdom (1.2%) [9] and, more surprisingly, Finland, where a 2.4% prevalence of CD was demonstrated by biopsy in a population of adults over fifty years of age [10] . The pediatric population was not analyzed in these studies, but prevalence of over 1%, even in older populations, is similar to that observed in pediatric studies.…”
Section: Epidemiologycontrasting
confidence: 52%
“…The major finding of this study is that CD is more prevalent in iron deficient females than in non-iron deficient females, which is in line with many different studies done in Europe [21,22] and Asia [8,23–25]. Also, the prevalence of CD in our patient population was 0.33% (1 in 303), which is lower than the results of studies in Europe [26–29]. …”
Section: Discussionsupporting
confidence: 85%
“…Breast feeding and the timing of gluten introduction in the diet [8], viral infections that promote the secretion of interferon alpha [9] and smoking [10] are some of the factors that appear to influence the development of the disease. Recently it has been recognized that CD is one of the most common diseases encountered by physicians, occurring in 0.5%-1% of the population [11][12][13].…”
Section: Introductionmentioning
confidence: 99%